Proteomic analysis of urinary proteins from patients with ovarian cancer and cervical cancer / Siti Suhana Abdullah Soheimi - Siti Suhana, Abdullah Soheimi (2012)
Diagnosis of ovarian carcinoma is in urgent need for new complementary biomarkers for early stage detection. In order to find an alternative procedure to replace an uncomfortable conventional method in detecting cervical cancer, a proteomic approach in screening the urinary proteins were employed. Proteins that are aberrantly excreted in the urine of cancer patients are excellent biomarker candidates for development of new non-invasive protocol for early diagnosis and screening purposes. In the present study, urine samples from patients with ovarian carcinoma and cervical cancer were analysed by two-dimensional gel electrophoresis (2-DE) and the profiles generated were compared to those similarly obtained from age-matched cancer negative women. These samples were also subjected to SELDI-TOF-MS as a complimentary technique for 2-DE especially on screening of aberrantly expressed of low molecular weight proteins.